Optimal Adaptation of the Use Conditions of Lateritic Soils in Flexible Pavements from Laboratory to the Construction Site - Baye Oumar Diop; Ignace Gbaguidi; Papa Goumbo Lo; Aminata Cisse; Seynabou Sène; Makhaly Ba (Challenging Issues on Environment and Earth Science Vol. 4, 2021)
In a dynamic of valorization, this study is carried out to appreciate the coarse elements influence of the gravel lateritic soils on the pavement behavior. The material involves not only the 0/20 mm granular particles considered in the specifications and on the laboratory tests, but also all of the material that is actually used in the construction sites. To face this challenge, geotechnical characterization was leaned on five differentiated granular classes of 0/20; 0/25; 0/31.5; 0/40 and 0/63 mm diameters. The sample of 0/40 mm gets the best compaction aptitude, while that of 0/31.5 mm reaches the greatest bearing strength and a good Optimum Moisture Content. According to the requirements and its bearing strengths, the material is usable up to subbase layer and its behavior depend to the grain size of its texture.